17 Using whole genome sequencing to make new diagnoses in paediatrics: successes, challenges and lifelong learning. (22nd November 2019) - Menzies, Lara; Morrogh, Deborah; Cullup, Thomas; Buckton, Andrew; Clement, Emma; Kumar, Ajith; Hurst, Jane
Abstract : Great Ormond Street Hospital has been a pioneer in offering Whole Genome Sequencing (WGS) to children with complex medical problems, for example through huge recruitment to the 100, 000 Genome Study. Genetic technologies herald great diagnostic promise for many children and access to WGS should increase with the launch of the new NHS Genomic Medicine Service. However, interpretation of genetic data and results is challenging. We present cases of new genetic diagnoses from the 100, 000 Genome Study which illustrate the revolutionary role WGS can provide in diagnosing children and identifying new genetic conditions, yet demonstrate that clinical acumen and an understanding of genetic technologies is still critical for diagnosis. Cohen syndrome is a genetic disorder characterised by intellectual impairment, developmental delay, microcephaly, and distinctive facial features, associated with homozygous alterations in the VPS13B gene. We describe two patients for whom a new diagnosis was confirmed only through a combination of clinical suspicion, microarray and WGS. Only a multi-pronged approach permitted recognition of a mono-allelic VPS13B deletion alongside a sequencing variant on the other allele. Geleophysic dysplasia is a rare skeletal dysplasia associated with heterozygous alterations in LTBP3. In-house clinical exome sequencing and WGS were both undertaken for a patient with a typical geleophysic phenotype. However, due to methodological differences, a likely pathogenic 32 base-pair duplication was only identified through one technique, emphasising the need for an appreciation of how genetic alterations can sometimes be missed without regular reappraisal, awareness of phenotype-genotype specificity, and an understanding of genomic methodology and caveats. Such cases highlight the importance of lifelong-learning in genomic medicine and why paediatricians should be aware of new developments, strengths and limitations of genetic testing. We propose that a new educational framework is required for clinicians and trainee doctors to maximise patient benefit from the new NHS Genomic Medicine Service.